Understanding impacts of “Russian Orientalism” on post-Soviet elite-management in the Republic of Bashkortostan - Demirtaş, Melih (Cappadocia Journal of Area Studies, 2020)
The “Russian Orient” has as emerged as a popular area of study for specialists and political analysts with a predominant interest in Russia and Eurasia-related affairs. My primary aim in this work will be specifically to look deeper into this concept of the “Orient” inside Russia’s vast geography. Simultaneously, I will place emphasis on the Russian “otherization” process within this huge spatial realm, drawing upon a remarkable case study on Bashkiria, or to use its current official name, the Republic of Bashkortostan, in the Russian Federation. I will pose one general question to garner information on the current situation in Bashkortostan, being “How can we understand the political elite management process in this Federative Republic as a successful part of a general Russian-led Orientalist project?” In trying to find an answer to this question throughout the work, like in the imperial era, and as observed in the Soviet centralized totalitarianism, the post-Soviet state understanding in Russia will be treated as a kind of a “success story” in terms of its incorporation of large and varied segments of its population into its “orbit”.